Beneficial effects of Oral Allspice,Pimenta dioicapowder supplementation on the hemato-immunological and serum biochemical responses ofOreochromis mossambicus - Ergün, Sebahatti̇n; Yilmaz, Sevdan; Türker, Ali̇; Agdamar, Sevan; Kesbi̇ç, Osman Sabri̇; Acar, Ümi̇t; Güllü, Kenan (Hindawi Limited, 2015)
The present study investigated the effects of dietary allspice powder supplementation on welfare status of Tilapia, Oreochromis mossambicus assessed by hemato-immunological and serum biochemical parameters. Five diets were formulated to contain 0 (control), 5, 10, 15 or 20 g of allspice kg 1 of fish feed. Fish were fed experimental diets for 60 days. Supplementation of allspice powder at 10 g kg 1 positively influenced the serum glucose, plasma lysozyme activity and myeloperoxidase activity. Dietary allspice powder at 15 g kg 1 also positively influenced the serum biochemical parameters (total protein, albumin and globulin) and plasma lysozyme activity. However, 20 g kg 1 allspice powder group had significantly lower values of respiratory burst activity and red blood cell count than other experimental groups (P < 0.05). In conclusion, the results of the present study demonstrated that supplementation of allspice powder at 10 or 15 g kg 1 for 60 days, had beneficial effects on improvement of some immunological and serum biochemical status of O. mossambicus. These findings suggest that dietary supplementation of allspice powder might further improve the resistance to fish pathogens.
Keywords: 2. Zero hunger; 3. Good health